Vitamin E concentration in human milk and associated factors: a literature review - Mayara S.R. Lima; Roberto Dimenstein; Karla D.S. Ribeiro (Brazilian Society of Pediatrics, 2014)
Objective: To systematize information about vitamin E concentration in human milk and the variables associated with this composition in order to find possible causes of deficiency, supporting strategies to prevent it in postpartum women and infants. Sources: Studies published between 2004 and 2014 that assayed alpha‐tocopherol in human milk of healthy women by high performance liquid chromatography were evaluated. The keywords used were "vitamin E", "alpha‐tocopherol", "milk, human", "lactation", "infant, newborn" equivalents in Portuguese, in the BIREME, CAPES, PubMed, SciELO, ISI Web of Knowledge, HighWire Press, Ingenta, and Brazilian Digital Library of Theses and Dissertations databases. Summary of the findings: Of the 41 publications found on the subject, 25 articles whose full text was available and met the inclusion criteria were selected. The alpha‐tocopherol concentrations found in milk were similar in most populations studied. The variable phase of lactation was shown to influence vitamin E content in milk, which is reduced until the mature milk appears. Maternal variables parity, anthropometric nutritional status, socioeconomic status, and habitual dietary intake did not appear to affect the alpha‐tocopherol levels in milk. However, the influence of the variables maternal age, gestational age, biochemical nutritional status in alpha‐tocopherol, and maternal supplementation with vitamin E had conflicting results in the literature. Conclusion: Alpha‐tocopherol concentration in milk decreases during lactation, until the mature milk appears. To confirm the influence of some maternal and child variables on milk vitamin E content, further studies with adequate design are needed.